COVID-19 risk perceptions among healthcare workers during early “new behavior norms” phase - Lolita Lolita; Azis Ikhsanudin (Intelektual Pustaka Media Utama, 2022)
The coronavirus disease 2019 (COVID-19) pandemic poses a serious health threat among Indonesian healthcare workers. As front-line workers, they were facing higher risk due to the prolonged exposure of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study aimed to explore various factors affecting perceived risk among healthcare professionals. A cross-sectional study was conducted among health practitioners who met the inclusion criteria of being over the age of 17 years and resided in Indonesia. This study was conducted during the early